A proinflammatory diet is associated with an increased likelihood of first clinical diagnosis of central nervous system demyelination in women. - Mannino, Adriana; Lithander, Fiona E; Dunlop, Eleanor; Hoare, Samuel; Shivappa, Nitin; Daly, Alison; Phillips, Michael; Pereira, Gavin; Sherriff, Jill; Lucas, Robyn M; Ponsonby, Anne-Louise; Hébert, James R; et al. (2022)
BACKGROUND: While a number of studies have examined associations between dietary factors and risk of multiple sclerosis (MS), little is known about intakes of inflammation-modulating foods and nutrients and risk of MS. OBJECTIVES: To test associations between the Dietary Inflammatory Index (DII®) and risk of a first clinical diagnosis of central nervous system (CNS) demyelination (FCD) (267 cases, 507 controls) using data from the Ausimmune Study. METHODS: The 2003-2006 Ausimmune Study was a multicentre, matched, case-control study examining environmental risk factors for an FCD, a common precursor to MS. The DII is a well-recognised tool that categorises individuals' diets on a continuum from maximally anti-inflammatory to maximally pro-inflammatory. The DII score was calculated from dietary intake data collected using a food frequency questionnaire. Conditional logistic regression models were used to estimate the association between DII and FCD separately for men and women. RESULTS: In women, a higher DII score was associated with increased likelihood of FCD, with a 17% increase in likelihood of FCD per one-unit increase in DII score (adjusted odds ratio 1.17, 95% confidence interval 1.04-1.33). There was no association between DII and FCD in men (adjusted odds ratio 0.88, 95% confidence interval 0.73-1.07). CONCLUSIONS: These findings suggest that a pro-inflammatory diet is associated with an increased likelihood of FCD in women.